Mapping the scientific research in ‘Independent Learning Independent Campus’ in years 2021-2022: a bibliometric review - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2022)
This study aims to analyze student perceptions of the technical, process and evaluation of learning at the Merdeka Learning Campus-Independent Campus (MBKM). This research is descriptive research with a qualitative approach by using VOSviewer. The research subjects were Non-formal Education Students at Muhammadiyah Enrekang University who participated in Internship activities. The instrument used is a questionnaire distributed via google form. The results obtained from this study are: 1) Students' perceptions of technical indicators in MBKM learning are positive; they do not experience signal problems and can easily access MBKM learning; 2) Students' perceptions of the indicators of the learning process in MBKM learning are on average positive; students can understand MBKM learning materials through discussion and communication between lecturers and students goes well; 3) Students' perceptions of the MBKM learning evaluation indicators are on average positive; students can do the midterm and final exams independently and students are satisfied with the implementation of MBKM learning so they are interested in taking it again in the next semester, but students feel that MBKM learning is not optimal because it is done online.